the Carbon - based materials derived from Phoenix Dactylifera (date palm) seeds, Magnifera Indica (mango) seeds, and Peltophorum Pterocarpum (Copper Pod) seeds were used in batch adsorption studies of fluoride. - KEERTHI GURANI; Dr. Shashikant R. Mise (PREPARE@u® | IEI Conferences, 2021)
Abstract - The removal of Fluoride from a synthetic sample by adsorption on physical activated carbon made from Phoenix Dactylifera (Date Palm) seeds, Magnifera Indica (Mango) seeds, and Peltophorum Pterocarpum (Copper Pod) seeds was carried out at room temperature of 32°C. 1oC. Batch studies were carried out on physically activated carbon to determine the best time, dosage, and pH for Fluoride removal. The best contact time, adsorbent dose, and pH for carbon were 40 minutes, 140 milligrammes, and 7.50, 40 minutes, 160 milligrammes, and 7.50, and 35 minutes, 120 milligrammes, and 7.50, with fluoride removal efficiency of 77.5 percent, 76.5 percent, 45 percent, 58 percent, 96 percent, and 78.96 percent, 87.99 percent, 97 percent, respectively.